Planning Issues and Sustainable Development - Newman, Peter (2015)
© 2015 Elsevier Ltd All rights reserved. There is a growing use of sustainable development by planners. The concept is being adopted without much controversy to create more holistic planning frameworks and community-based planning processes. However, there is no clear agreement on what sustainability means in terms of city size, urban form, and transportation. The debates are summarized and some resolution suggested.